Thermal expansion coefficient of carbon‐supported Pt nanoparticles: In‐situ X‐ray diffraction study. Issue 5 (4th January 2017) - Leontyev, I. N.; Kulbakov, A. A.; Allix, M.; Rakhmatullin, A.; Kuriganova, A. B.; Maslova, O. A.; Smirnova, N. V.
Abstract : The thermal expansion of carbon‐supported Pt nanoparticles with different particle size has been studied in‐situ via X‐ray diffraction at temperatures from 100 to 300 K. The thermal expansion coefficient (TEC) of investigated Pt/C nanoparticles is always superior to that of bulk Pt. When the grain size D decreases from 11 to 3 nm, the TEC nonlinearly increases by about 1.66 × 10 −6  K −1 which corresponds to a variation of ∼20% from bulk Pt. The obtained experimental dependence of TEC for Pt/C nanoparticles has been interpreted using different theoretical approaches. A comparison of the considered models with the experimental data reveals the best agreement from the binding order–length–strength model with the size dependence of TEC experimentally found in carbon‐supported Pt nanoparticles.